The use of mammals in the settlement of the 1st and 2nd iron age of Santa Olaia (Figueira da Foz): DOI: https://doi.org/10.5281/zenodo.7920514 - Martins, Filipe (2023)
We present the results of a study of the faunistic assemblages of the 1st and 2nd Iron Age collected at the excavations in the settlement of Santa Olaia (Figueira da Foz). The study seeks to contribute to the knowledge to the economy and diet of the Phoenicians populations who inhabited the site situated in the ancient estuary of the Mondego river, as well as the populations that succeeded them, throughout the second half of the first millennium BC.